Supercapacitive Performance of Ordered Mesoporous Carbon (CMK-3) in Neutral Aqueous Electrolyte - Seyed Mahmoud Mousavi Safavi; Mohammad Ali Kiani (Iranian Journal of Chemistry & Chemical Engineering, 2018)
Ordered Mesoporous Carbon (OMC) represents an interesting material for electric double layer capacitors which has the high surface area, easily accessed ordered pore channels and lower production cost. In this work, CMK-3 as promising OMC has been fabricated using the ordered mesoporous silica SBA-15 as a template. The structure and morphology of CMK-3 are characterized by X-ray diffraction, nitrogen adsorption/desorption, and scanning electron microscopy. CMK-3 is sprayed on the surface of highly conductive three-dimensional nickel foam and characterized as an electrode for electric double layer capacitors. When this electrode is soaked in a neutral aqueous electrolyte solution, reaches a specific capacitance as high as 285 and 167 F/g, at a current density of 10 and 34 A/g, respectively. CMK-3 shows excellent long-term stability with >90% capacitance retention after 10000 cycles, as well as high power (37 kW/kg) and energy density (98 Wh/kg).